PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEPUTUSAN KEUANGAN DAN NILAI PERUSAHAAN - Latifah Anom; Eni Susilowati; Benny Nur Azis; Vita Tri Setyowati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2016)
This study aims to determine the influence of ownership structure on firm value of debt policy as an intervening variable. Data used in this research is secondary data obtained from Indonesia Stock Exchange database. This study used the path analysis to analysze and interprete the data of research. From the results of data analysis can be concluded that in Indonesia (1) the ownership structure proxied by insider ownership has relationship with financial decisions; (2) ownership structure has not affect stock prices, as a proxy of firm value; (3) there is no influence of ownership structure on corporate value through debt policy and as an intervening variable.